Cultural Communication in Wayang Sada and Preservation of Local Values - Adiprabowo, Vani Dias (Institut Komunikasi dan Bisnis LSPR, 2024)
Wayang Sada, as a form of traditional Javanese performing arts, faces significant challenges in maintaining its relevance amid the growing tide of globalization. The main problem faced is how to maintain the interest of the younger generation in Wayang Sada in the midst of the onslaught of foreign cultural values supported by the development of modern technology and entertainment. This research aims to explore the role of Wayang Sada as a medium of cultural communication as well as efforts to preserve local values in the context of modernization. The research method used is qualitative with a case study approach, which focuses on an in-depth analysis of the phenomenon of Wayang Sada in the Special Region of Yogyakarta. The results of the study show that although Wayang Sada has great potential in shaping the character of the younger generation through the local wisdom values contained in it, there is a significant gap in its integration strategy into the lives of the current young generation. The conclusion of this study is that Wayang Sada needs innovation and adaptation in cultural presentation and communication in order to attract the interest of the younger generation, while maintaining the preservation of local cultural values in the midst of the challenges of globalization.